2023
DOI: 10.1051/0004-6361/202244914
|View full text |Cite
|
Sign up to set email alerts
|

Temperature of quiet Sun small scale brightenings observed by EUI on board Solar Orbiter: Evidence for a cooler component

Abstract: Context. On May 30, 2020, small and short-lived extreme-UV (EUV) brightenings in the quiet Sun were observed over a four-minute sequence by the EUV channel of the Extreme Ultraviolet Imager – High Resolution Imager (EUIHRIEUV) on board the Solar Orbiter. The brightenings’ physical origin and possible impact on coronal or transition region (TR) heating are still to be determined. Aims. Our aim is to derive the statistical thermal evolution of these events in order to establish their coronal or TR origin. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
2
0
0
Order By: Relevance
“…Compared with the DEM results in Berghmans et al (2021), who reported that EUI brightenings can reach coronal temperature, our cases are more likely to have a lower temperature. A similar result can be found in Dolliou, A. et al (2023), who conducted a time-lag analysis of EUI brightenings. This measures the time delays between the light curves of different AIA channels.…”
Section: Discussionsupporting
confidence: 82%
“…Compared with the DEM results in Berghmans et al (2021), who reported that EUI brightenings can reach coronal temperature, our cases are more likely to have a lower temperature. A similar result can be found in Dolliou, A. et al (2023), who conducted a time-lag analysis of EUI brightenings. This measures the time delays between the light curves of different AIA channels.…”
Section: Discussionsupporting
confidence: 82%
“…Compared with the DEM results in Berghmans et al (2021), who reported that EUI brightenings can reach coronal temperature, our cases are more likely to have a lower temperature. A similar result can be found in Dolliou et al (2023), who conducted a time-lag analysis of EUI brightenings. This measures the time delays between the light curves of different AIA channels.…”
Section: Discussionsupporting
confidence: 82%